2013
DOI: 10.1016/j.jcv.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of noroviruses associated with acute sporadic gastroenteritis in children: Global distribution of genogroups, genotypes and GII.4 variants

Abstract: Molecular epidemiology of noroviruses associated with acute sporadic gastroenteritis in children: global distribution of genogroups, genotypes and GII.4 variants 小児の急性胃腸炎の原因としてのノロウイルスの分子疫学: ゲノグループ、ゲノタイプ GII.4 変異株の世界的分布

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
143
5
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 236 publications
(173 citation statements)
references
References 126 publications
21
143
5
1
Order By: Relevance
“…In Brazil, GII.4 NoV is most frequently reported from emergency departments [5,6,29,30]. The presence of a variety of genotypes in Sergipe and the periodic shift of GII.4 variants (i.e., GII.4 New-Orleans_2009 and GII.4 Sydney_2012) reflects the emergence worldwide of GII.4 variants [29,[31][32][33][34][35][36], confirming that the NoV genotypes have a wide geographical distribution. The increased detection of GII.4 could be explained by GII.4 theoretically causing more severe disease than other genotypes [31,37], but GII.4 diarrhoea severity in our patients was similar to other genotypes and we do not have evidence of an increased severity.…”
Section: Discussionmentioning
confidence: 93%
“…In Brazil, GII.4 NoV is most frequently reported from emergency departments [5,6,29,30]. The presence of a variety of genotypes in Sergipe and the periodic shift of GII.4 variants (i.e., GII.4 New-Orleans_2009 and GII.4 Sydney_2012) reflects the emergence worldwide of GII.4 variants [29,[31][32][33][34][35][36], confirming that the NoV genotypes have a wide geographical distribution. The increased detection of GII.4 could be explained by GII.4 theoretically causing more severe disease than other genotypes [31,37], but GII.4 diarrhoea severity in our patients was similar to other genotypes and we do not have evidence of an increased severity.…”
Section: Discussionmentioning
confidence: 93%
“…A study from Alberta, Canada, showed that GI NoVs were responsible for ϳ37% of all NoV infections from late 2012 to early 2013, with the majority being caused by GI.6 and GI. 7. This was an ϳ15-fold-higher prevalence than in 2010 (12).…”
mentioning
confidence: 79%
“…Nevertheless, most human NoV infections are caused by genogroups GI and GII. Furthermore, in the last 2 decades, genotype GII.4 has been the causative agent of Ͼ95% of NoV gastroenteritis outbreaks, with globally distributed epidemic viral variants emerging every 2 to 3 years (11,12).…”
Section: Importancementioning
confidence: 99%
“…Nevertheless, most human NoV infections are caused by genogroups GI and GII. Furthermore, in the last 2 decades, genotype GII.4 has been the causative agent of Ͼ95% of NoV gastroenteritis outbreaks, with globally distributed epidemic viral variants emerging every 2 to 3 years (11,12).NoVs are small nonenveloped viruses with a nonsegmented single-stranded positive-sense RNA genome, which encodes the viral structural and nonstructural proteins in three open reading frames (ORFs). ORF1 encodes the six nonstructural proteins, including the viral protease and the RNA-dependent RNA polymerase (RdRp), while ORF3 encodes a small basic protein, VP2, which interacts with VP1 and stabilizes the virion (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation